2018
DOI: 10.1016/j.jhin.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between airborne and surface microbes in the critical care environment?

Abstract: Passive air sampling provides quantitative data analogous to that obtained from surfaces. Settle plates could serve as a proxy for routine environmental screening to determine the infection risk in ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 20 publications
1
41
1
1
Order By: Relevance
“…Mean bioburden levels recorded in this study are lower than those from other ICU studies which have reported levels between 350 and 450 cfu/m 3 [18,19], and higher than those from a more recent study (<40 cfu/m 3 ) [20]. The differences are likely due to confounding factors including differences in air change ventilation rates, number of medical staff and patients, patient conditions and, importantly, the sample number and collection times.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Mean bioburden levels recorded in this study are lower than those from other ICU studies which have reported levels between 350 and 450 cfu/m 3 [18,19], and higher than those from a more recent study (<40 cfu/m 3 ) [20]. The differences are likely due to confounding factors including differences in air change ventilation rates, number of medical staff and patients, patient conditions and, importantly, the sample number and collection times.…”
Section: Discussioncontrasting
confidence: 83%
“…All airborne microbes ultimately end up depositing on to surrounding surfaces, and so can contribute indirectly to infection transmission via direct surface contact. A recent study aimed to establish a correlation between air and surface microbes in the critical care environment, further emphasizing this phenomenon [20]. Their research found a strong association between passive air sampling counts and surface counts, and made the important point that surface bacteria will include a portion of airborne bacteria after settling.…”
Section: Discussionmentioning
confidence: 99%
“…This commentary summarises the study; why it was performed, how it was performed, and the main results, which were published in a sequence of three papers by the authors of this article [2][3][4]. The findings suggest the main direction of travel for the study pathogen, S. aureus, as well as highlighting the most important reservoirs in an ICU.…”
Section: Introductionmentioning
confidence: 98%
“…At the Gaweye district hospital in Niamey, the biocleaning was done with only detergents that are difficult to provide by officials (sometimes provided by their agents funds). This low level of cleanliness was confirmed by the presence of Staphylococcus aureus in all contact media analyzed (Beggs et al, 2014, Dallolio et al, 2017, Smith et al, 2018, Agodi et al,2015, Fauci et al, 2017.…”
Section: Discussionmentioning
confidence: 84%